Estratégias de marketing na internacionalização das pequenas e médias empresas baianas: uma análise do setor de vestuário - Costa, Bernardo Gonçalves da (2006)
This research aims to identify and evaluate marketing and branding strategies adopted by Bahia s small and medium clothing exporters and analyze how these strategies support their internationalization process. In this study, the survey method was used to get data from six exporting companies. The results indicate that the companies are in the beginning of their internationalization process and the strategies adopted are still fallible. The study also show which strategy has been obtaining better results. As conclusion, in order to these companies obtain better results in their internationalization processes it s necessary to align marketing strategies with branding strategies